2017
DOI: 10.3892/mmr.2017.7981
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effect of hesperidin modulates inflammatory responses and antioxidant status following acute myocardial infarction through the expression of PPAR‑γ and Bcl‑2 in model mice

Abstract: Hesperetin is the main pharmacological ingredient of fruit of the citrus family, rutaceae. It is a flavanone, which has potent antioxidation and anti‑inflammatory activities. The present study investigated the preventive effect of hesperidin in the modulation of acute myocardial infarction (AMI)‑induced inflammatory responses and antioxidant status in a mouse model. The levels of creatine kinase‑MB, tumor necrosis factor (TNF‑α), interleukin (IL)‑1β, IL‑6, monocyte chemoattractant protein 1 (MCP‑1), intercellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 33 publications
1
12
0
Order By: Relevance
“…In one reported literature, Wu et al has demonstrated inhibitory effects of embelin on colitis‐associated cancer through reducing an increased level of NF‐κB, TNF‐α, and IL1β . In another study, Meng et al have shown an anti‐inflammatory and antioxidant effect of embelin in myocardial infarction .…”
Section: Discussionmentioning
confidence: 99%
“…In one reported literature, Wu et al has demonstrated inhibitory effects of embelin on colitis‐associated cancer through reducing an increased level of NF‐κB, TNF‐α, and IL1β . In another study, Meng et al have shown an anti‐inflammatory and antioxidant effect of embelin in myocardial infarction .…”
Section: Discussionmentioning
confidence: 99%
“…Citrus flavonoids have been shown to reduce cardiovascular disease prominently due to their antioxidant effects [33]. In this regard, hesperidin, abundant flavanone glycoside present in citrus fruits, has been demonstrated to modulate the inflammatory responses and antioxidant status following acute myocardial infarction and could be considered as a promising candidate to alleviate cardiotoxic effect of doxorubicin [34]. In addition, hesperitin, the aglycone of hesperidin, has a cardioprotective effect increasing GHS levels and preventing oxidative DNA damage in rat models [35].…”
Section: Discussionmentioning
confidence: 99%
“…Another citrus flavonoid, nobiletin, shows effects on lipogenesis, inhibiting the accumulation of liver lipids by acting on lipogenic factors such as SREBP-1c and FAS [17]. Hesperidin also modulates the inflammatory response and antioxidant status through the downregulation of PPARγ and Bcl-2 expression in mice [18]. Curcumin, quercetin, and atorvastatin also regulate the expression of lipogenic genes, such as CPT1, and generally protect against liver fibrosis by reducing the accumulation of liver fat [19].…”
Section: Discussionmentioning
confidence: 99%